SINTESIS PERANCAH HIDROKSIAPATIT BERPORI DARI LIMBAH CANGKANG KERANG MENGGUNAKAN METODE REPLIKASI SPONS POLYURETHANE - Fitri Afriani; Anisa Indriawati; Widodo Budi Kurniawan; Yekti Widyaningrum; Rifqi Almusawi Rafsanjani; Yuant Tiandho (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2020)
Researchers have synthesized hydroxyapatite-based porous scaffolds by the polyurethane sponge replication methods. Hydroxyapatite was derived from waste cockle shells through the co-precipitation method. The synthesis of porous scaffolds through the sponge replication methods is carried out by absorbing hydroxyapatite slurry through the addition of PVA and then followed by heating at 900oC to decompose the polyurethane and PVA. The best of slurry that can produce a porous scaffold in this study is the slurry that prepared through the ratio of hydroxyapatite:PVA = 80:20. The decomposition of the two polymers will leave macropores on the scaffold with an average size of 460 μm. Based on the thermogravimetric analysis, X-ray diffraction and FTIR spectrophotometer revealed that the PVA and polyurethane sponge were correctly decomposed, except for scaffolds with 40% PVA. Thus, the porous scaffolds synthesized in this study satisfies the requirements of porous scaffolds for the bone therapy process.